Education management according to the perspective of the quran - Gunawan Nasution, Putra Mahendra (Jurnal Ilmu Pendidikan dan Humaniora, 2025)
This research aims to analyze the concept of education management in the perspective of the Qur'an with a focus on its functions and implementation in the Islamic education system. The research method used is library research with a descriptive qualitative approach, where the main sources analyzed are the verses of the Qur'an and related literature. The results of the study show that the study of education management from the perspective of the Qur'an is important, because the Qur'an as the main source of Islamic teachings, contains divine principles that can be used as a guideline in the management of education holistically and based on monotheism, justice, and morals. In addition, the concept of human beings as caliphs provides the basis for moral and spiritual responsibility in leading and managing a meaningful education system. Although much has been done on education management, approaches that directly link modern managerial functions to Quranic values are still limited, so this research offers novelty by developing an Islamic education management model that is applicable and relevant to contemporary educational challenges, such as digitalization and moral crises. The practical implications of this research include strengthening Islamic leadership, developing a curriculum based on spiritual values, improving educator competence, using technology ethically, and strengthening collaboration between schools, families, and communities. With this approach, the Islamic education system is expected to be able to produce a generation with noble character and ready to face the challenges of the times